1999
DOI: 10.1063/1.478535
|View full text |Cite
|
Sign up to set email alerts
|

Fully coupled six-dimensional calculations of the water dimer vibration-rotation-tunneling states with split Wigner pseudospectral approach. II. Improvements and tests of additional potentials

Abstract: Fully coupled 6D calculations of the ammonia vibration-inversion-tunneling states with a split Hamiltonian pseudospectral approach J. Chem. Phys. 111, 7236 (1999); 10.1063/1.480099Six-dimensional quantum calculation of the intermolecular bound states for water dimer Fully coupled six-dimensional calculations of the water dimer vibration-rotation-tunneling states with a split Wigner pseudo spectral approachThe SWPS method is improved by the addition of H.E.G. contractions for generating a more compact basis. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 73 publications
6
81
0
Order By: Relevance
“…Our work on the Ar-benzene complex, 102-104 the ammonia dimer, 53 and the water dimer [56][57][58][59][60][61][62] has shown that the comparison of calculated VRT levels with experimental (high-resolution) spectroscopic data is an excellent way to check and, if needed, improve the quality of intermolecular potential surfaces. Although much experimental data is available also for the benzene dimer, most of these data consists of UV, Raman, and infrared spectra that address the properties of the (perturbed) monomers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work on the Ar-benzene complex, 102-104 the ammonia dimer, 53 and the water dimer [56][57][58][59][60][61][62] has shown that the comparison of calculated VRT levels with experimental (high-resolution) spectroscopic data is an excellent way to check and, if needed, improve the quality of intermolecular potential surfaces. Although much experimental data is available also for the benzene dimer, most of these data consists of UV, Raman, and infrared spectra that address the properties of the (perturbed) monomers.…”
Section: Discussionmentioning
confidence: 99%
“…The methods that have been developed [53][54][55][56][57] to compute the VRT states of a weakly bound dimer start from the Hamiltonian of a rotating dimer with two internally rotating (rigid) polyatomic monomers, expressed in body-fixed (BF) dimer coordinates…”
Section: Computational Methods a Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently have rigorous models for the dimer potential and rigorous methods for computing concentrations from them been developed. [18][19][20] Recent measurements 2,21 have shown that the absorption of solar flux at dimer vibrational overtone wavelengths predicted in ref 2 is negligibly small. 1,21 However, the very recent article by Pfeilsticker et al 22 reports measured dimer atmospheric absorption the intensities of which are in agreement with values determined via a combination of calculated water dimer line strengths by Low and Kjaergaard 23 and the classic laboratory experiments of Curtiss et al 24 Their results are lower than absorption intensities determined using our results for K P calculated on the original VRT(ASP-W) potential.…”
Section: Introductionmentioning
confidence: 99%